Predictive Value of Initial 18F-FDG PET/CT for Identifying EGFR and KRAS Mutations in Patients with Non-small-cell Lung Cancer - Ozge Vural Topuz; Nur Buyukpinarbasili (Haseki Tıp Bülteni)
Aim: Since the importance of epidermal growth factor receptor (EGFR) and Kirsten rat sarcoma viral oncogene homolog gene (KRAS) mutation status in predicting treatment response in non-small cell lung cancer (NSCLC) patients is well known, we aimed to evaluate whether initial fluorine-18-fluorodeoxyglucose (18F-FDG) positron emission tomography-computed tomography (PET/CT) imaging could non-invasively predict EGFR or KRAS mutation states in this patient group. Methods: This retrospective observational study examined patients with NSCLC who underwent 18F-FDG PET/CT for staging from August 2021 to January 2024. Age, sex, smoking status, pathological data, EGFR and KRAS mutation status, and metabolic and volumetric PET parameters were recorded. Groups were based on gene mutation status as follows: EGFR-mutations (mt) vs. EGFR wild-type (EGFR-wt) and KRAS-mt vs. KRAS-wt. Results: Ninety-nine patients with a mean age of 62.96±9.66 (range: 37-87) were included. The EGFR-mt group had lower metabolic tumor volume (MTV) (p=0.015) and total lesion glycolysis (TLG) (p=0.017) values. MTV had an area under the receiver operating characteristic curve (AUC) of 0.667 [95% confidence interval (CI): 0.547-0.788, p=0.015], and with a ≤24.9 cut-off, yielded 60.87% sensitivity, 68.42% specificity, and 66.67% accuracy to detect EGFR-mt. For TLG, the AUC was 0.664 (95% CI: 0.540-0.788, p=0.017) and a ≤408.1 cut-off yielded 86.96% sensitivity, 43.42% specificity, 53.54% accuracy, and 91.67% NPV. KRAS-mt was detected in 34 (34.34%) patients, and there were no significant differences between the KRAS-mt and KRAS-wt groups in terms of PET parameters. Conclusion: Primary tumor parameters derived from initial 18F-FDG PET/CT can predict EGFR mutation status but not KRAS mutation status. The high negative predictive value of TLG can be used to rule out EGFR-mt status, possibly preventing unnecessary treatments in patients without favorable genetic properties, especially when genetic analyses are not possible.